The power-capture of a nearshore, modular, flap-type wave energy converter in regular waves. (1st June 2017) - Wilkinson, L.; Whittaker, T.J.T.; Thies, P.R.; Day, S.; Ingram, D.
Abstract: Bottom-hinged, nearshore flap-type wave energy converters (WECs), have several advantages, such as high power conversion efficiency and survivability. They typically comprise a single flap spanning their full width. However, a potentially beneficial design change would be to split the flap into multiple modules, to make a 'Modular Flap'. This could provide improvements, such as increased power-capture, reduced foundation loads and lower manufacturing and installation costs. Assessed in this work is the hydrodynamic power-capture of this device, based on physical modelling. Comparisons are made to an equivalent 'Rigid Flap'. Tests are conducted in regular, head-on and off-angle waves. The simplest control strategy, of damping each module equally, is employed. The results show that, for head-on waves, the power increases towards the centre of the device, with the central modules generating 68% of the total power. Phase differences are also present. Consequently, the total power produced by the Modular Flap is, on average, 23% more smooth than that generated by the Rigid Flap. The Modular Flap has 3% and 1% lower average power-capture than the Rigid Flap in head-on and off-angle waves, respectively. The advantages of the modular concept may therefore be exploited without significantly compromising the power-capture of the flap-type WEC. Highlights: Physical modelling of a modular flap considers viscous effects. Power increases significantly towards the central modules. A modular flap has 3% lower efficiency than a rigid flap in head-on waves. Power generated by a modular flap is 23% more smooth. A modular flap has up to 10% higher efficiency in off-angle waves.